Memaknai Poster Penyelamatan Satwa WWF - Rezca Utama Arza; Sumekar Tanjung (Asian Journal of Innovation and Entrepreneurship, 2021)
The purpose of this study was to describe various messages contained in poster visual design on creative campaigns carried out by the World Wildlife Fund. In this study, researchers used semiotic analysis with a descriptive qualitative approach developed by Charles S. Pierce, where researchers classified the signs on the poster of the World Wildlife Fund into three parts, namely icons, index, and symbols. There are two visual poster designs analyzed. The results of the study showed that the poster designs made by the World Wildlife Fund discuss several important aspects that have relevance to this case. The first is the aspect of criticism of the government that criticizes the government's attitude towards the environment of wildlife damage. The second aspect is the social and cultural aspects that cause environmental damage because people still hold local culture and traditions in their hometown. The last aspect is the aspect of environmental preservation which is at the core of all movements carried out by the World Wildlife Fund to show that the animal extinction rate is even bigger and encourage the community to preserve the environment for the survival of animals.